2020
DOI: 10.1111/dom.14139
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of the fixed‐ratio combination of insulin glargine 100 units/mL and lixisenatide (iGlarLixi) in Japanese people with type 2 diabetes: A subgroup and time‐to‐control analysis of the LixiLan JP phase 3 trials

Abstract: Aims To explore the impact of baseline characteristics on clinical outcomes in the phase 3 LixiLan JP trials which evaluated the efficacy and safety of iGlarLixi, a titratable fixed‐ratio combination of insulin glargine 100 units/mL (iGlar) and GLP‐1 RA lixisenatide (Lixi), vs Lixi (JP‐O1, NCT02749890) or iGlar (LixiLan JP‐O2, NCT02752828; JP‐L, NCT02752412) in Japanese people with type 2 diabetes uncontrolled on oral antidiabetes drugs (OADs; JP‐O1, JP‐O2) or OADs and basal insulin (JP‐L). Materials and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
5
5
0
Order By: Relevance
“…In these previous analyses, iGlarLixi was associated with significantly greater HbA1c reductions compared with iGlar or Lixi among participants in both age subgroups (<65 and ≥65 years) 33,34 . Similar to the current analysis, regardless of age, the incidence of documented symptomatic hypoglycaemia with iGlarLixi was generally similar to that with iGlar and the incidence of gastrointestinal AEs was lower with iGlarLixi versus Lixi 33,34 . In addition to the findings of the current post hoc analysis, iGlarLixi had non‐inferior glycaemic efficacy and superior efficacy with regard to weight change to that of premixed 30% insulin aspart plus 70% insulin aspart protamine (BIAsp 30) in the global SoliMix study in people with uncontrolled T2D on BI plus OAD therapy, including participants aged ≥65 years and those with T2D for ≥10 years 35 …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In these previous analyses, iGlarLixi was associated with significantly greater HbA1c reductions compared with iGlar or Lixi among participants in both age subgroups (<65 and ≥65 years) 33,34 . Similar to the current analysis, regardless of age, the incidence of documented symptomatic hypoglycaemia with iGlarLixi was generally similar to that with iGlar and the incidence of gastrointestinal AEs was lower with iGlarLixi versus Lixi 33,34 . In addition to the findings of the current post hoc analysis, iGlarLixi had non‐inferior glycaemic efficacy and superior efficacy with regard to weight change to that of premixed 30% insulin aspart plus 70% insulin aspart protamine (BIAsp 30) in the global SoliMix study in people with uncontrolled T2D on BI plus OAD therapy, including participants aged ≥65 years and those with T2D for ≥10 years 35 …”
Section: Discussionsupporting
confidence: 77%
“…33,34 Similar to the current analysis, regardless of age, the incidence of documented symptomatic hypoglycaemia with iGlarLixi was generally similar to that with iGlar and the incidence of gastrointestinal AEs was lower with iGlarLixi versus Lixi. 33,34 In addition to the findings of the current post hoc analysis, iGlarLixi had non-inferior glycaemic efficacy and superior efficacy with regard to weight change to that of premixed 30% insulin aspart plus 70% insulin aspart protamine (BIAsp 30) in the global SoliMix study in people with uncontrolled T2D on BI plus OAD therapy, including participants aged ≥65 years and those with T2D for ≥10 years. 35 The limitations of the current analysis include its post hoc nature, which means that this analysis is not powered to evaluate the primary endpoint, in particular in those subgroups with a low number of participants.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…39 The current study demonstrates that lixisenatide as add-on therapy to basal insulin is effective in an Asian population, irrespective of BMI, and confirms previous data that lixisenatide efficacy is independent of BMI from studies in Caucasian or Japanese individuals with diabetes. [40][41][42] The results of this analysis are in line with other analyses conducted in individuals receiving other GLP-1 receptor agonists. Studies of both liraglutide 43 44 and exenatide [45][46][47][48][49] indicate that baseline BMI values are not predictive of the reduction in HbA1c seen with these treatments.…”
Section: Multivariable Regression Analysissupporting
confidence: 85%
“…As a result of a lack of clinically significant benefits, combining a DPP-4i and GLP-1 RA is not recommended [15], and typically DPP-4is are discontinued before initiating a GLP-1 RA or fixed-ratio combination containing a GLP-1 RA component. In this study, the analysis of the prior DPP-4i exposure on outcomes was conducted to confirm that switching from a DPP-4i to iGlarLixi does not lead to a deterioration in glycaemic control in clinical practice, and to confirm prior clinical trial data [16]. This analysis showed that prior DPP-4i use did not affect the HbA1c-lowering effect of iGlarLixi, did not negatively affect body weight during iGlarLixi treatment, and did not appear to impact changes in the iGlarLixi dose.…”
Section: Discussionmentioning
confidence: 93%